The social psychology of humor - Strick, Madelijn 1979-; Ford, Thomas E. (Routledge, Taylor & Francis Group, 2021)
"This important new book provides a comprehensive analysis of humor from a social-psychological perspective, addressing questions about the use of humor and its effects in daily life. It examines the social psychology of humor on micro level phenomena, such as attitudes, persuasion, and social perception, as well as exploring its use and effect on macro level phenomena such as conformity, group processes, cohesion and intergroup relations. Humor is inherently a social experience, shared among people, essential to nearly every type of interpersonal relationship. In this accessible volume, Strick and Ford review current research and new theoretical advancements to identify pressing open questions and propose new directions for future research in the social psychology of humor. The book explores fascinating topics such as humor in advertising, political satire, and the importance of a sense of humor in maintaining romantic relationships. It also examines how racist or sexist humor can affect personal and intergroup relations, and discusses how to confront inappropriate jokes. Offering new, precise and operational conceptions of humor in social processes, this book will be essential reading for students and academics in social psychology, and media and communication studies"
Keywords: Sozialpsychologie; Analyse; Humor; Wit and humor / Psychological aspects; Wit and humor / Social aspects; Social psychology; Aufsatzsammlung